2019
DOI: 10.1111/dmcn.14149
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on health and development: nutrition, substance exposure, and adverse childhood experiences

Abstract: Scientific advances over the last century have generated compelling evidence of the primary and secondary effects of gestational, infant, and childhood conditions. These early environmental influences have the potential not only to impact an individual's health outcomes, such as heart disease, type 2 diabetes, and cancer, but also to confer various protections and risks to that individual's descendants. The immediate and extended ramifications of early environmental exposure bring an understanding of epidemiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
(80 reference statements)
0
22
0
Order By: Relevance
“…Women with GDM have an increased risk of developing obesity, metabolic disease, and type 2 diabetes in later life [3]. Furthermore, the "developmental origins of health and disease (DOHaD)" theory proposes intergenerational consequences where the offspring of mothers with GDM have an increased risk of obesity and metabolic syndrome during childhood and later in life [32].…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…Women with GDM have an increased risk of developing obesity, metabolic disease, and type 2 diabetes in later life [3]. Furthermore, the "developmental origins of health and disease (DOHaD)" theory proposes intergenerational consequences where the offspring of mothers with GDM have an increased risk of obesity and metabolic syndrome during childhood and later in life [32].…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…size of prefrontal cortex) and function (e.g. dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis), the multi-system involvement of these variables within the human body, and the contextual importance of environmental factors for any such variables or systems, there are many pathways which could potentially result in an ACE-adult diet quality (as represented by the HEI-10) association (19,(29)(30)(31)(32)(33)(34) .…”
Section: Introductionmentioning
confidence: 99%
“…Overwhelmingly, the last 30+ years of DOHaD‐related research has confirmed this basic idea that early life environment influences health and disease risks across the lifespan 4 . This body of work has also elucidated many of the physiological and biochemical mechanisms that link developmental exposures with subsequent disease risks 3–7 …”
Section: What Is the Developmental Origins Of Health And Disease Frammentioning
confidence: 91%
“…4 This body of work has also elucidated many of the physiological and biochemical mechanisms that link developmental exposures with subsequent disease risks. [3][4][5][6][7] The foregoing description of a developmental framework may sound familiar to readers who have not previously encountered the acronym "DOHaD" because it reflects a core concept from evolutionary biology used regularly by evolutionary anthropologists: ontogenetic or developmental plasticity. 8 Developmental plasticity is the tendency for developing organisms to adjust non-canalized aspects of their growth strategies in response to environmental stimuli.…”
Section: What Is the Developmental Origins Of Health And Disease Frmentioning
confidence: 99%
See 1 more Smart Citation